Electrospinning Method Used to Create Functional Nanocomposites Films 2018
DOI: 10.5772/intechopen.77221
|View full text |Cite
|
Sign up to set email alerts
|

The Place of Electrospinning in Separation Science and Biomedical Engineering

Abstract: Electrospunnanofibers have found myriad of applications from separation science to clinical translation. Electrospunnanofiber scaffolds have the benefits of unique properties such as high surface area to volume ratio, interfibrous pore sizes, strong penetrability, great deal of active sites for adsorption, excellent stability, better targeting, minimum toxicity, high drug-loading capacity, exceptional mechanical properties, flexibility in surface functionality, ease of encapsulation of drugs and bioactive comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 91 publications
(298 reference statements)
0
3
0
Order By: Relevance
“…The induced electrical forces to surpass the surface tension of the charged liquid followed by the transformation of the pendant drop shape of the liquid meniscus into a “Taylor cone” shape. The whipping and bending instability upon charging the liquid produces a jet of ultrafine fibers before reaching the collector as electrospun fibers [ 18 , 19 , 20 , 21 ]. Upon the electrospinning process, the deposited nanofiber mesh is usually collected as sheets of 10–30-mm-thickness, on top of a conductive substrate.…”
Section: Introductionmentioning
confidence: 99%
“…The induced electrical forces to surpass the surface tension of the charged liquid followed by the transformation of the pendant drop shape of the liquid meniscus into a “Taylor cone” shape. The whipping and bending instability upon charging the liquid produces a jet of ultrafine fibers before reaching the collector as electrospun fibers [ 18 , 19 , 20 , 21 ]. Upon the electrospinning process, the deposited nanofiber mesh is usually collected as sheets of 10–30-mm-thickness, on top of a conductive substrate.…”
Section: Introductionmentioning
confidence: 99%
“…[22,23] Short time of drying for traveling fibers prior reaching to the collector surface and low stretching forces applied on them are among the reasons for such undesirable outcomes. [22] On the other hand, lower feeding rates will provide enough time for solution polarization. [24] It has been experimentally demonstrated that applying a high voltage during electrospinning process, as a crucial factor, leads to production of fibers with larger diameters.…”
mentioning
confidence: 99%
“…[21] Enhancing the feeding rate usually will lead to production of thick fibers and also bead formation. [22,23] Short time of drying for traveling fibers prior reaching to the collector surface and low stretching forces applied on them are among the reasons for such undesirable outcomes. [22] On the other hand, lower feeding rates will provide enough time for solution polarization.…”
mentioning
confidence: 99%